2014
DOI: 10.1002/qj.2395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ERA‐Interim reanalysis precipitation products using England and Wales observations

Abstract: Precipitation forecast data from the ERA-Interim reanalysis (33 years) are evaluated using the daily England and Wales Precipitation (EWP) observations obtained from a rain-gauge network. Observed and reanalysis daily precipitation data are both described well by Weibull distributions with indistinguishable shapes but different scale parameters, such that the reanalysis underestimates the observations by an average of 22%. The correlation between the observed and ERA-Interim time series of regional daily preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 38 publications
5
43
0
Order By: Relevance
“…This comparison used as observations the CRU TS3.1 from the Climate Research Unit at the University of East Anglia (Mitchell and Jones, ), which consists of monthly statistical interpolations of ground stations in a 5 decimal degree grid. Similarly, ERA‐Interim over‐predicted daily precipitation in the UK by 20% compared with observations (England and Wales Precipitation (EWP); De Leeuw et al ., ). Further, in China, fits of ERA‐Interim data to observations of 755 meteorological sites were poor with average R 2 values for 10 catchments ranging from 0.28 to 0.55 (Fu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This comparison used as observations the CRU TS3.1 from the Climate Research Unit at the University of East Anglia (Mitchell and Jones, ), which consists of monthly statistical interpolations of ground stations in a 5 decimal degree grid. Similarly, ERA‐Interim over‐predicted daily precipitation in the UK by 20% compared with observations (England and Wales Precipitation (EWP); De Leeuw et al ., ). Further, in China, fits of ERA‐Interim data to observations of 755 meteorological sites were poor with average R 2 values for 10 catchments ranging from 0.28 to 0.55 (Fu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Fluxes which are computed from the forecasts as accumulations suffer from 'spin-up' from the initial state. Previous work analysing precipitation (e.g., Kobold and Sušelj 2005;Simmons et al 2010;Kållberg 2011;Hawcroft et al 2012;de Leeuw et al 2014;Hawcroft et al 2015) has shown that lead times between 12-24 h are less affected by this problem. Therefore data at 3-hourly intervals extracted from the period 12-24 h in each successive forecast are combined to create each season of data (see Hawcroft et al 2015, Figure 11).…”
Section: Erai Reanalysismentioning
confidence: 96%
“…Uncertainty in the reanalysis data (e.g., Boilley and Wald, ; Nkiaka et al, ) may affect the results. However, quite good performance of the ERA‐Interim dataset has been found in previous studies (e.g., de Leeuw et al, ; Bumke, ; Nkiaka et al, ). For example, Nkiaka et al .…”
Section: Model Description and Methodologymentioning
confidence: 99%